Short-Term Effects and Early Complications of Balloon-Occluded Retrograde Transvenous Obliteration for Gastric Varices. (5th December 2012) - Watanabe, Manabu; Shiozawa, Kazue; Ikehara, Takashi; Nakano, Shigeru; Kougame, Michio; Otsuka, Takafumi; Kikuchi, Yoshinori; Ishii, Koji; Igarashi, Yoshinori; Sumino, Yasukiyo
Abstract : The short-term effects of balloon-occluded retrograde transvenous obliteration (BRTO) to treat gastric varices were evaluated by using computed tomography (CT) and gastroscopy (GF). The subjects were 77 patients who underwent BRTO to treat gastric varices. The short-term effects of BRTO were investigated with regard to ascites, pleural effusion, venous thrombus, and esophageal varices by comparing the findings of CT and GF performed within one month before and after BRTO. The mean duration of followup was 960.1 days. Ascites and pleural effusion were exacerbated after BRTO in 26 (33.8%) and 31 (40.3%), respectively. A significant difference in ascites exacerbation was noted in patients with hypoalbuminemia and a high Child-Pugh score, and a significant difference in exacerbation of pleural effusion was noted in patients with hypoalbuminemia. Venous thrombus was noted in 7 patients (9.1%). Esophageal varices were exacerbated in 14 (21.2%) of the 66 patients. The 2-year survival rate was 720 days, and significant differences were noted in the Child-Pugh classification and the concomitance of hepatocellular carcinoma (HCC) on multivariate analysis of prognosis-related factors. Conclusion . The frequencies of exacerbation of ascites, pleural effusion, and esophageal varices after BRTO were high but these may not be related to survival.